Evolution of Class Management: Advancing with the Times - Zhou, Longjun (Science Insights Education Frontiers, 2025)
Class management, an important component of the education system, evolves with the changes in social needs and educational paradigms in various historical phases. Before the wide adoption of class-based teaching, individual-specific instruction predominated in education in the long history of small-scale farming- and crafts-dominated social production (Tian, 2009). Still, there were certain preliminary experiments with class-based instruction in the early times. For instance, ancient Romans had tried it in the first century AD, which was praised by the educationist Quintilian, who strongly argued for the advantages of this teaching form (Wang et al, 1993). In the twelfth century, boarding became popular in the U.K.’s schools such as Oxford and Cambridge, with which came the “mentoring system,” where the mentors were responsible for supporting students in knowledge acquisition and cognitive development, as well as in moral, spiritual, aesthetic, and physical growth. Their roles were parallel to those of today’s homeroom teachers (Ban, 1996). In the fifteenth and sixteenth centuries, classical secondary schools in Western European countries organized their students into classes by age. The renowned educationist Erasmus of that time first advanced the concept of “class” (Jin, 1993).